Visual Strategy Analysis of Indomie Advertising and Its Influence on YouTube Audiences - Nadila Putri; Muhammad Teddy Abadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study analyzes the visual strategies used in the Indomie advertisement titled “Akan Kuhadapi Dunia, Tapi Indomie Goreng Jumbo Dulu!” and their influence on audiences on YouTube. Indomie is one of Indonesia’s most recognized instant noodle brands, known for consistent and emotionally resonant visual advertising. This research employs a descriptive qualitative approach with supporting quantitative engagement data from YouTube metrics. The data object is a 15-second digital advertisement uploaded to the official Indomie Indonesia YouTube channel. Visual elements—including color, typography, layout, character expression, product display, and cinematographic technique—were analyzed using the AIDIA (Attention, Interest, Desire, Information, Action) framework. Engagement data (views, likes, comments) were gathered as supporting indicators of audience response. Results indicate that Indomie’s visual strategy effectively employs the full AIDIA cycle: the brand’s signature colors (red, yellow, green) capture immediate attention; a relatable stress-relief narrative sustains interest; close-up food photography generates desire; concise product packaging shots convey information; and massive engagement (over 65 million views) confirms audience action. The study concludes that a cohesive visual communication strategy combining color identity, emotional narrative, and food aesthetics is central to Indomie’s digital advertising effectiveness. These findings offer practical guidance for visual communication designers and digital marketers seeking to maximize audience engagement on social media platforms.